(untitled) - National Safety Council (Boston, 2005)
The Basic First Aid is the go-to reference for emergencies that no home will want to be without. Full of practical, clear, and easy-to-understand advice, this resource ensures that every household is prepared for any type of medical situation. Includes line drawings and instructions to help people through emergency situations, as well as a medical information chart that everyone should have on hand.
Keywords: First aid in illness and injury,Sơ cứu bệnh tật và chấn thương